Kritik Terhadap Green Economy dalam Praktik Pembangunan di Negara - Koerniawan, Rina Nurlaeli Rachmawati; Umar, Genius (Trends in Applied Sciences, Social Science, and Education, 2025)
This study aims to analyze the application of the green economy concept in the development of the education, tourism, and recreation sectors in Palangka Raya City, as well as the challenges faced by the government in supporting sustainable development. The method used in this study is a qualitative descriptive approach through literature studies and documentation. The results of the study indicate that the application of the green economy in the education sector encourages the integration of environmentally based curriculum and strengthening student awareness of sustainability issues. In the tourism and recreation sector, the principles of the green economy are implemented through the management of ecotourism-based destinations and the preservation of the natural environment. However, challenges such as limited human resources, inadequate infrastructure, and cross-sector coordination are still major obstacles. In addition, this study also revealed that the application of the green economy contributes significantly to the reduction of greenhouse gas emissions and the achievement of several sustainable development goals (TPB/SDGs), especially in environmental aspects. Therefore, synergistic efforts are needed between the government, society, and the private sector to optimize the implementation of the green economy in Palangka Raya.